Motor learning methodological decisions analysis and reflexion on sports teaching methdology (Revista Paulista de Educação Física, 1989)
The author studies reading matters published over the past 25 years concerning beaviour and methodological action in a physical education class followed by guidance and decisions for physical education teachers* performance in a Movement Learning Programme